1987
DOI: 10.1007/bf02439579
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking by women: interactions with alcohol use

Abstract: Cigarette smoking increased during alcohol self-administration in comparison to an alcohol-free baseline in 24 women given access to alcohol for 21 days. Heavy smokers (25 or more cigarettes per day) increased smoking significantly during drinking (P less than 0.05). Analysis of tobacco smoking by level of alcohol consumption showed that both heavy and moderate alcohol users increased smoking significantly during alcohol availability (P less than 0.05, 0.01). The heavy and moderate smokers smoked significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 24 publications
3
55
2
Order By: Relevance
“…It is possible that those with greater nicotine dependence were more reactive to tobacco following alcohol consumption. Studies of light, social drinkers have demonstrated either minimal (Henningfield et al, 1984) or modest increases in smoking behavior following alcohol consumption (Mello et al, 1987), suggesting that the influence of drinking on smoking behavior may be more pronounced in heavier drinkers. In addition to our stated focus on understanding lapse behavior in abstaining smokers, this study may also have relevance for understanding the influence of alcohol on ongoing smoking behavior in those not attempting cessation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that those with greater nicotine dependence were more reactive to tobacco following alcohol consumption. Studies of light, social drinkers have demonstrated either minimal (Henningfield et al, 1984) or modest increases in smoking behavior following alcohol consumption (Mello et al, 1987), suggesting that the influence of drinking on smoking behavior may be more pronounced in heavier drinkers. In addition to our stated focus on understanding lapse behavior in abstaining smokers, this study may also have relevance for understanding the influence of alcohol on ongoing smoking behavior in those not attempting cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Human laboratory studies have examined the effect of smoked tobacco on alcohol use (Barrett et al 2006;Madden et al 1995;Mello et al 1980Mello et al , 1987 as well as the effect of nicotine deprivation on the reinforcing value of alcohol (Colby et al 2004;Cooney et al 2003;Palfai et al 2000;Perkins et al 2000a). Fewer studies have tested the effect of nicotine replacement on subjective alcohol responses (Cooney et al 2001;Kouri et al 2004;Perkins et al 1995) and alcohol self-administration behavior (Acheson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For the current study, we were interested in examining the effect of transdermal nicotine replacement on subjective and physiological responses to a low-dose priming drink of alcohol and subsequent self-administration behavior in a sample of heavy-drinking daily smokers. While alcohol-nicotine interactions have been documented in lighter users (e.g., Barrett et al 2006), it has been suggested that the nature of these interactions may be more pronounced in those with heavier use (e.g., Henningfield et al 1984;Mello et al 1987). We enrolled individuals with heavier patterns of alcohol and cigarette use (15-25 cigarettes per day; at least nine drinks per week for females; at least 12 drinks per week for males) than the Acheson et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic women with premenstrual symptoms have been shown to increase their alcohol consumption premenstrually under controlled laboratory conditions (Mello et al 1990). Women with premenstrual symptoms have also been shown to smoke more marijuana or tobacco cigarettes premenstrually, suggesting that this subpopulation of women may be at increased risk to use a variety of drugs (Mello and Mendelson 1985;Mello et al 1987). Thus, a second purpose of this study was to determine if women who suffered from PMS were at risk to misuse or abuse benzodiazepines.…”
mentioning
confidence: 99%